The Effect of Extraction Methods on the Total Phenols and Total Flavonoids Content of Jackfruit (Artocarpus heterophyllus Lamk) Peels Extract - Dyan Wigati; Lindawati Setyaningrum; Dwi Koko Pratoko (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
Jackfruit (Artocarpus heterophyllus Lamk), especially the flesh usually consumed in a ripe state. The jackfruit peel is a non-edible waste. The research aims to determine the effect of different extraction methods on the total phenolic content and total flavonoid content of jackfruit peel extract. Extraction methods are percolation, maceration, and digestion. The total phenolic content (TPC) and total flavonoid content (TFC) using a spectrophotometer with AlCl3 and Folin-ciaocalteu reagents. Rutin and gallic acid as a standarts. The data from various extraction methods were analyzed statistically by One-Way Anova. The results showed TPC values by percolation, maceration, and digestion respectively 5.94 ± 0.92; 3.03 ± 0.16 and 2.72 ± 0.22 (GAE mg/g). The TFC respectively 13.04 ± 0.38; 5.49 ± 0.33 and 4.16 ± 0.28 (RTE mg/g). Statistical analysis showed that there were significant differences (p < 0.05) in the levels of flavonoids and total phenolics between various extraction methods from the ethanol extract of jackfruit peel. The percolation method showed the highest TPC, TFC, and yield rather than other methods.